Modern Slavery and Human Trafficking - Reeves, Jane (IntechOpen, 2021)
This edited volume, Modern Slavery and Human Trafficking, is a collection of reviewed and relevant research chapters, offering a comprehensive overview of recent developments in the field of modern slavery and human trafficking. The book comprises single chapters authored by various researchers and edited by an expert active in the aforementioned research area. Each chapter is complete in itself but united under a common research study topic. This publication aims at providing a thorough overview of the latest research efforts by international authors on modern slavery and human trafficking, and opening new possible research paths for further novel developments.